2021
DOI: 10.3390/su132111863
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender Stereotypes, Type of Sport Watched and Close Environment on Adolescent Sport Practice According to Gender

Abstract: The practice of sport by adolescents is influenced by multiple factors, which could create differences in sports participation according to gender. The objectives of this study were to determine which types of sports were most practiced by adolescent males and females; and to analyze the relationship of gender stereotypes, the type of sport observed and the personal environment, to the type of sport practiced, depending on the adolescent’s gender. To this end, a total of 632 adolescents completed the questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
5
0
4
Order By: Relevance
“…However, previous studies have shown that early maturers develop a series of physical and anthropometric capacities as a result of the maturational effect, including being taller than normal and late maturers during this period of growth [ 61 , 62 ]. This aspect could be a competitive advantage in sports involving strength, power, speed, agility, and endurance [ 63 ], i.e., most competitive sports played by adolescents, including basketball, football, and martial arts [ 64 , 65 ]. Also in those sports that are usually practiced in Physical Education sessions within the school environment, among which volleyball, basketball, handball, and football stand out [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that early maturers develop a series of physical and anthropometric capacities as a result of the maturational effect, including being taller than normal and late maturers during this period of growth [ 61 , 62 ]. This aspect could be a competitive advantage in sports involving strength, power, speed, agility, and endurance [ 63 ], i.e., most competitive sports played by adolescents, including basketball, football, and martial arts [ 64 , 65 ]. Also in those sports that are usually practiced in Physical Education sessions within the school environment, among which volleyball, basketball, handball, and football stand out [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la relación entre el género y el tipo de deporte, un estudio realizado en la Región de Murcia (España) investigó qué tipos de deportes eran los más populares entre adolescentes masculinos y femeninos para determinar la relación entre los estereotipos de género, el tipo de deporte y el entorno de los y las adolescentes (Mateo-Orcajada et al, 2021). Otro estudio analizó cómo se representaban determinados deportes como masculinos, femeninos y/o sin género entre estudiantes universitarios del noreste de los Estados Unidos (Sobal & Milgrim, 2019).…”
Section: Género Y Tipo De Deporteunclassified
“…In terms of the relation between gender and sport type, a study conducted in the Murcia Region of Spain investigated which sports types were the most popular among adolescent males and females in order to determine the relationship between gender stereotypes, the kind of sport, and the adolescents' environment (Mateo-Orcajada et al, 2021). Another study considered how particular sports were represented as masculine, feminine and/or neither-gendered between undergraduate students in the northeast US (Sobal & Milgrim, 2019).…”
Section: Gender and Sport Typementioning
confidence: 99%